BIMBINGAN TEKNIS PEMBUATAN MEDIA BUKU DIGITAL BAGI GURU BAHASA INDONESIA - Rahmawati Mulyaningtyas; Lilis Anifiah Zulfa; Muyassaroh; Ristu Wahyu Stiawan (LPPM IAI Hasanuddin Pare-Kediri, 2023)
Teachers need to equip themselves with the ability to develop learning media, especially those which are based on computer technology. The purpose of this public service activity is to explain technical matters related to the making of digital books by Indonesian language teachers. Then, to explain the obstacles to the making of digital books by Indonesian language teachers during the technical workshop activities. This public service activity uses the PAR (participatory action research) method. This method is aimed that Indonesian language teachers add the insights and be able to practice the making of digital books using the Flip PDF Professional application. Participants of this technical workshop are Indonesian language teachers from the MI, SMP/MTs, SMA/MA/SMK levels of 20 people. Based on the needs analysis, information was obtained that Indonesian language teachers were not optimal in the making of learning media, especially digital books. This is caused by the digital books used so far are in PDF format. The results of the public service show that the participants can follow the activities well. However, there are several obstacles during the activity, especially connectivity limitations while installing the applications or using the applications because they require internet access.